Biomechanical Analysis of Laparoscopic Incisional Gastropexy With Intracorporeal Suturing Using Knotless Polyglyconate. Issue 1 (11th March 2014) - Imhoff, Darren J.; Cohen, Andrea; Monnet, Eric
<x xml:space="preserve">Abstract</x> Objective To evaluate load to failure of laparoscopic incisional gastropexy performed with intracorporeal suturing using knotless polyglyconate (KP). Study Design Cadaveric study. Animals Canine cadavers (n = 12). Methods Laparoscopic incisional gastropexy using 2 strands of KP was performed in 6 canine cadavers and by an open approach in 6 cadavers. Length of the gastropexy, number of suture bites on each side of the gastropexy, and number of inadvertent full thickness gastric suture bites were recorded. Load to failure was measured. Results There was no significant difference in mean (±SD) gastropexy load to failure for the open (46.3 ± 19.6 N) and laparoscopic (69.0 ± 26.0 N) approaches (P = .123). No significant differences between laparoscopic and open approaches were detected for mean stomach (3.1 ± 0.1 cm; 3.0 ± 0.2 cm; P = .353) or abdominal wall (3.1 ± 0.2 cm; 3.0 ± 0.2 cm; P = .553) incision lengths. There was no significant difference between groups for number of suture bites medially (P = .448) or laterally (P = .363). There were 3 instances of a single gastric intraluminal suture for the laparoscopic group and none for the open approach (P = .023). Conclusion Incisional gastropexy performed with laparoscopic intracorporeal suturing and KP has a load to failure that is comparable with an open method. Load to failure was similar to reported values for open incisional gastropexy with knotless glycomer 631.